“I can’t do it”: A qualitative study exploring case and contact experiences with COVID-19 contact tracing - Tyler Shelby; Cailin Arechiga; Amanda J. Gupta; Rachel Hennein; Christopher Schenck; Brian Weeks; Maritza Bond; Linda Niccolai; J. Lucian Davis; Lauretta E. Grau (BMC Public Health, 2022)
Abstract Background Low engagement in contact tracing for COVID-19 dramatically reduces its impact, but little is known about how experiences, environments and characteristics of cases and contacts influence engagement. Methods We recruited a convenience sample of COVID-19 cases and contacts from the New Haven Health Department’s contact tracing program for interviews about their contact tracing experiences. We analyzed transcripts thematically, organized themes using the Capability, Opportunity, Motivation, Behavior (COM-B) model, and identified candidate interventions using the linked Behavior Change Wheel Framework. Results We interviewed 21 cases and 12 contacts. Many felt physically or psychologically incapable of contact tracing participation due to symptoms or uncertainty about protocols. Environmental factors and social contacts also influenced engagement. Finally, physical symptoms, emotions and low trust in and expectations of public health authorities influenced motivation to participate. Conclusion To improve contact tracing uptake, programs should respond to clients’ physical and emotional needs; increase clarity of public communications; address structural and social factors that shape behaviors and opportunities; and establish and maintain trust. We identify multiple potential interventions that may help achieve these goals.